1997
DOI: 10.1103/physreva.56.4864
|View full text |Cite|
|
Sign up to set email alerts
|

Superfluid state of atomic6Liin a magnetic trap

Abstract: We report on a study of the superfluid state of spin-polarized atomic 6 Li confined in a magnetic trap. Density profiles of this degenerate Fermi gas and the spatial distribution of the BCS order parameter are calculated in the local-density approximation. The critical temperature is determined as a function of the number of particles in the trap. Furthermore, we consider the mechanical stability of an interacting twocomponent Fermi gas, in the case of both attractive and repulsive interatomic interactions. Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
305
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(321 citation statements)
references
References 30 publications
(59 reference statements)
16
305
0
Order By: Relevance
“…A mechanical instability of a strongly interacting Fermi gas arises when attractive interactions overcome repulsive effects such as the Fermi pressure [3]. In actual experimental realizations [10], there are mechanisms not represented by the simple model Eq.…”
Section: Ground Statementioning
confidence: 99%
“…A mechanical instability of a strongly interacting Fermi gas arises when attractive interactions overcome repulsive effects such as the Fermi pressure [3]. In actual experimental realizations [10], there are mechanisms not represented by the simple model Eq.…”
Section: Ground Statementioning
confidence: 99%
“…It has even been shown that a two-component gas of spin-polarized atomic 6 Li becomes superfluid at experimentally obtainable densities and temperatures [4]. This is due to the fact that 6 Li has an anomalously large and negative s-wave scattering length a, with a recent measurement giving a ≃ −2160a 0 where a 0 is the Bohr radius [5]. s-wave scattering is forbidden for two fermions in the same spin-state, but, the 6 Li atom has six hyperfine states.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity we have considered here a non-interacting Fermi gas, but it is clear that this method can be extended to study the effects of interactions onto the fermionic excitation spectrum. In particular we plan to address the consequences of Cooper pairing of the fermions [5,23,24,25] in a subsequent paper.…”
mentioning
confidence: 99%